Perancangan dan Pembuatan Sistem Informasi Administrasi pada Katering Happuch - Albert Kristian Dupa; Silvia Rostianingsih; Leo Willyanto Santoso (Jurnal Infra, 2014)
Happuch Catering is a catering service ordering food for an event, generally weddings and seminars. Happuch Catering is a catering which puts the quality of service and excellent flavors. So to calculate inventory can charge so much mind to business owners who are basically in the implementation of business owners do it manually or just follow his intuition about the amount of material required. So, we need an information system that provides accurate information. Based on the background of these problems, the designed system administration information. System design process from application through several stages, starting with a survey catering systems, data analysis and designing the Data Flow Diagram and Entity Relationship Diagram of the application to be made. The implementation process uses Microsoft Visual Studio .Net in 2005 as the programming language and Microsoft SQL Server as the database.The results obtained from the application that has been made, among others, can store all data related to the process of ordering, purchasing of materials, calculation of profit and loss, as well as reports.